Prognosis-related novel immunostaining pattern for programmed cell death ligand 1 and prognostic value of tumour-infiltrating lymphocytes in triple-negative breast cancer - Savaş, Pınar; Serin, Gürdeniz; Gürsoy, Pınar; Zekioğlu, Osman; Özdemir, Necmettin (Polish Journal of Pathology, 2023)
This study aims to determine the prognostic significance of programmed cell death ligand 1 (PD-L1) expression and tumour-infiltrating lymphocytes (TILs) in triple- negative breast cancer (TNBC). PD-L1 expression and TIL percentage were determined in TNBCs that did not receive neoadjuvant therapy. The relationship between PD-L1 expression and the percentage of TILs with survival was investigated. The presence of intratumoural PD-L1-positive tumour-infiltrating immune cells (TIICs) in tumours with ≥ 1% PD-L1 expression was identified as a new PD-L1 evaluation parameter. The presence of intratumoural PD-L1-positive TIICs as a new parameter in PD-L1-positive cases increased overall survival. The percentage of TILs increased in both overall and distant metastasis-free survival (p = 0.040 and p = 0.006, respectively). As a result, it was found that the risk of death was increased 5.18-fold (p = 0.013) in patients without intratumoural PD-L1-positive TIICs. This risk of death was calculated to be 5.40-fold higher in patients with TIL percentage ≤ 10% than in those with > 40% (p = 0.024), and the risk of distant metastasis was calculated to be 11.95 times higher. In our study, we discovered that the percentage of TILs made a statistically significant difference in TNBC survival. The presence of intratumoural PD-L1-positive TIICs in PD-L1-positive cases significantly increased survival.